Perylenediimide/Graphite Foil‐Based Electrode Materials with Outstanding Cycling Stability for Symmetric Supercapacitor Device Architectures. Issue 6 (29th April 2022) - Biradar, Madan R.; Kale, Amol M.; Kim, Byung Chul; Bhosale, Sidhanath V.; Bhosale, Sheshanath V.
Abstract : Herein, pyridine functionalized naphthalenediimide (NDI‐Py) and perylenediimide (PDI‐Py) derivatives are synthesized and characterized using modern techniques. NDI‐Py and PDI‐Py in combination with graphite foil (GF) are employed as electrode materials for supercapacitor (SC) applications. Under the three‐electrode system, the electrode materials based on NDI‐Py/GF and PDI‐Py/GF composite electrode exhibit specific capacitance ( C sp ) of about 118 and 179 F g −1 at 5 mV s −1 from cyclic voltammetry (CV) and 132 and 197 F g −1 at 1 A g −1 from galvanostatic charge–discharge (GCD) curves. The electrochemical performance behaviors of these electrodes are mainly contributed by surface reactions along with the Faradaic redox reactions such as pseudocapacitance. The corresponding two‐electrode symmetric SC device based on PDI‐Py/GF//PDI‐Py/GF exhibits a high energy density of 46 Wh kg −1 at a power density of 3060 W kg −1 at 1 A g −1 current density, which is further retained at 13 Wh kg −1 and 15 300 W kg −1 energy and power density, respectively, at 5 A g −1 current density. Moreover, the symmetrical SC device based on PDI‐Py/GF//PDI‐Py/GF shows outstanding cyclic stability for 10 000 charge–discharge cycles while maintaining 95% of the original capacitance. Abstract : Pyridine functionalized naphthalenediimdie and perylenediimide molecular architecture in combination with graphite foil are employed to fabricate organic supercapacitor devices. PDI‐Py/GF//PDI‐Py/GF‐based symmetric supercapacitor displays outstanding long‐term cycling stability with remarkable initial capacitance retention of about 95% after 10 000 cycles. PDI‐based material is a strong candidate for fabrication of supercapacitors with long‐cycling stability.